Optimal parameters to avoid thermal necrosis during bone drilling: A finite element analysis. Issue 11 (2nd March 2017) - Mediouni, Mohamed; Schlatterer, Daniel R.; Khoury, Amal; Von Bergen, Tobias; Shetty, Sunil H.; Arora, Manit; Dhond, Amit; Vaughan, Neil; Volosnikov, Alexander
ABSTRACT: The drilling bone may potentially cause excessive frictional heat, which can lead to local bone necrosis. This heat generation and local necrosis has been suggested to contribute to the resorption of bone around the placed screws, ending in loss of screw purchase in the bone and inadvertent loosening and/or the bone‐implant construct. In vivo studies on this subject have inherent obstacles not the least of which is controlling the variables and real time bone temperature data acquisition. Theoretical models can be generated using computer software and the inclusion of known constants for the mechanical properties of metal and bone. These known Data points for the variables (drill bit and bone) enables finite element analysis of various bone drilling scenarios. An elastic–plastic three‐dimensional (3D) acetabular bone mode was developed and finite element model analysis (FEA) was applied to various simulated drilling procedures. The FEA results clearly indicate that the depth of drilling and the drill speed both have a significant effect on the temperature during drilling procedures. The reduction of the feeding speed leads to a reduction in bone temperature. Our data suggests that reducing the feeding speed regardless of RPMs and pressure applied could be a simple useful and effective way to reduce drilling temperatures. This study is the first step in helping any surgeon who drills bone and places screws to better understand the ideal pressure to apply and drill speed to employ and advance rate to avoid osteonecrosis. © 2017 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 35:2386–2391, 2017. Abstract : A pelvic model and FEA defined variables to reduce heat generation and its consequence (threshold is 50°C), bone necrosis. The FEA data has three never before reported findings. (i) When drilling 3 mm of cortical bone at a constant rotation of 600 rev/min. feeding 1 mm/s produces a force of 50–80 Newton (N) and 75°C temperature; and (ii) Reducing the feeding speed to 0.1 mm/s, the temperature reduced to 39°C, with constant axial force and rotation of 600 rev/min.